2014
DOI: 10.1021/jf503393h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Ultrasound and Cooling Rate on the Crystallization Behavior of Beeswax in Edible Oils

Abstract: The objective of this study was to evaluate the effect of wax concentration (0.5 and 1%), cooling rate (0.1, 1, and 10 °C/min), and high-intensity ultrasound (HIU) on the crystallization behavior of beeswax (BW) in six different edible oils. Samples were crystallized at 25 °C with and without HIU. Crystal sizes and morphologies and melting profiles were measured by microscopy and differential scanning calorimetry, respectively, after 7 days of incubation. Higher wax concentrations resulted in faster crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 21 publications
6
41
0
Order By: Relevance
“…This is expected as the size of the crystals decreases (see microscopy results below), more surface area is available to entrap the surrounding oil compared to a network composed of crystals with larger size. Similar results were reported by Blake and Marangoni (), who achieved the decrease in crystal size by increasing cooling rate on wax oleogels, and by Jana and Martini (), who found that smaller crystals were obtained when HIU was used in beeswax oleogels. Furthermore, it is interesting to note that the increment in OBC as cooling rate increased was greater in nonsonicated than in sonicated samples for all concentrations, with average values of 28% and 15%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…This is expected as the size of the crystals decreases (see microscopy results below), more surface area is available to entrap the surrounding oil compared to a network composed of crystals with larger size. Similar results were reported by Blake and Marangoni (), who achieved the decrease in crystal size by increasing cooling rate on wax oleogels, and by Jana and Martini (), who found that smaller crystals were obtained when HIU was used in beeswax oleogels. Furthermore, it is interesting to note that the increment in OBC as cooling rate increased was greater in nonsonicated than in sonicated samples for all concentrations, with average values of 28% and 15%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…1b suggests that RBW and PW did not co-crystallize, a careful analysis of the melting enthalpies of the samples (data not shown) indicates that some degree of partial cocrystallization occurred in this system, which supports the monotectic behavior depicted in Fig. Some of the important physical properties include the texture, structural organization, and strength of the crystalline network formed [13][14][15][16]. If we compare the previous two type of diagrams, binary wax-based product formulation can be easily understood.…”
Section: Pseudo-phase Diagramssupporting
confidence: 54%
“…There is a small difference in the eutectic phase diagram in Fig. Other authors have reported similar 100 % BW crystal morphology [16,17]. The solidus line in this eutectic diagram is curved upwards towards a higher percentage of SFW/PW.…”
Section: Pseudo-phase Diagramssupporting
confidence: 49%
“…The acquired results confirmed the previous hypothesis; smaller crystals lead to a stronger gel which is more capable to retain oil in their mixture. According to Jana & Martini (), HIU can delay phase separation in beeswax organogel during storage. Chen et al .…”
Section: Resultsmentioning
confidence: 97%